Coats disease in female population: A comparison of clinical presentation and outcomes - Piquin, Gwendoline; Chapron, Thibaut; Abdelmassih, Youssef; Martin, Gilles; Edelson, Catherine; Caputo, Georges; Metge, Florence (Frontiers in Medicine, 2022)
Purpose To compare clinical characteristics at presentation and outcomes of Coats disease between females and males. Methods In this retrospective, consecutive case series we included all children diagnosed with Coats disease in a single tertiary referral center. Initial clinical presentation, treatment and outcomes were collected. Results A total of 158 children were included, of whom 29 (18.3%) were females and 11 (6.9%) had bilateral involvement. Age at diagnosis and disease stage were similar between females and males. Females had more bilateral involvement (p < 0.001) and tended to have a worse visual acuity at diagnosis (p = 0.05). At last follow-up, visual acuity and anatomical outcome after treatment were similar between genders. Conclusion Female patients with Coats disease had more bilateral involvement and tended to have worse visual acuity at presentation. Clinical presentation and outcomes seemed to be similar between genders.